Using Media to Teach Religious Studies - Roth, Mirko (Journal for religion, film and media, 2017)
In terms of media theories, teaching religious studies provides a second-order mediatisation of religious phenomena - a mediatisation of phenomena already mediatised by religious traditions. That tension needs to be reflected upon, as it raises a number of questions before we even reach the classroom. Furthermore, in class another tension comes to light, between teaching objectives and their limits. By formulating a hypothesis and problematising these tensions, this article develops a strategy based on the application of a concept of competence acquisition. How this strategy might look in a teaching scenario is demonstrated from an introductory seminar on Islam.